2016
DOI: 10.1242/dmm.026591
|View full text |Cite
|
Sign up to set email alerts
|

Poor maternal nutrition and accelerated postnatal growth induces an accelerated aging phenotype and oxidative stress in skeletal muscle of male rats

Abstract: ABSTRACT‘Developmental programming’, which occurs as a consequence of suboptimal in utero and early environments, can be associated with metabolic dysfunction in later life, including an increased incidence of cardiovascular disease and type 2 diabetes, and predisposition of older men to sarcopenia. However, the molecular mechanisms underpinning these associations are poorly understood. Many conditions associated with developmental programming are also known to be associated with the aging process. We therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 44 publications
4
46
0
Order By: Relevance
“…; Tarry‐Adkins et al . ). The altered metabolic processes demonstrated here in the MO‐F1 such as decreased insulin signalling would support the view that MO shortens offspring lifespan.…”
Section: Discussionmentioning
confidence: 97%
“…; Tarry‐Adkins et al . ). The altered metabolic processes demonstrated here in the MO‐F1 such as decreased insulin signalling would support the view that MO shortens offspring lifespan.…”
Section: Discussionmentioning
confidence: 97%
“…; Tarry‐Adkins et al . , ; Vaiserman, ). Most studies on ageing compare only two categorical life course time points.…”
Section: Introductionmentioning
confidence: 99%
“…Both programming outcomes (Desai et al 2015) and ageing processes (Chahal & Drake, 2007) have been shown to result in metabolic and endocrine dysfunction and increased oxidative stress. This study addresses the urgent need for studies that determine interactions between programming and ageing mechanisms (Rodriguez-Gonzalez et al 2014;Rodriguez-Gonzalez et al 2015;Tarry-Adkins et al 2016Vaiserman, 2018). Most studies on ageing compare only two categorical life course time points.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Tarryadkins et al . () have shown that oxidative stress and inflammation usually accompany the compensatory growth of rats. Therefore, the elevated expression of Tnf‐α in the jejunum of rats in the LN group indicated chronic inflammation as a cost of the rapid growth rate.…”
Section: Discussionmentioning
confidence: 99%